A First Example of a Lyotropic Smectic C* Analog Phase Design, Properties and Chirality Effects - Bruckner, Johanna. R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
In this thesis Johanna Bruckner reports the discovery of the lyotropic counterpart of the thermotropic SmC* phase, which has become famous as the only spontaneously polarized, ferroelectric fluid in nature. By means of polarizing optical microscopy, X-ray diffraction and electro-optic experiments she firmly establishes aspects of the structure of the novel lyotropic liquid crystalline phase and elucidates its fascinating properties, among them a pronounced polar electro-optic effect, analogous to the ferroelectric switching of its thermotropic counterpart. The helical ground state of the mesophase raises the fundamental question of how chiral interactions are "communicated" across layers of more or less disordered and achiral solvent molecules which are located between adjacent bi-layers of the chiral amphiphile molecules. This thesis bridges an important gap between thermotropic and lyotropic liquid crystals and pioneers a new field of liquid crystal research.
Introduction -- Aims and scope of this thesis -- Thermotropic and lyotropic liquid crystals -- Materials and experimental techniques -- Results and discussion -- Summary -- References -- Appendix A -- Appendix B.
Keywords: Physical chemistry; Soft condensed matter; Analytical chemistry; Crystallography; Physical Chemistry; Soft and Granular Matter; Analytical Chemistry; Crystallography and Scattering Methods